Disease predisposition of human leukocyte antigen class II genes influences the gut microbiota composition in patients with primary biliary cholangitis - Huang, Chun-Yang; Zhang, Hai-Ping; Han, Wei-Jia; Zhao, Dan-Tong; Liao, Hui-Yu; Ma, Yin-Xue; Xu, Bin; Li, Li-Juan; Han, Ying; Liu, Xiu-Hong; Wang, Qi; Lou, Jin-Li; et al. (Frontiers in Immunology, 2022)
Background The human leukocyte antigen (HLA) susceptibility gene is the main genetic risk factor for primary biliary cholangitis (PBC). The prognosis of patients with PBC is linked to gut microbiota dysbiosis. However, whether the HLA alleles are associated with the gut microbiota distribution and disease severity remains unknown. Methods A cohort of 964 Chinese patients with PBC was enrolled at Beijing YouAn Hospital, Beijing, China. High-resolution genotyping of the HLA class I and class II loci from 151 of these patients was performed using sequence-based PCR. Stool samples were collected from 43 of the 151 fully HLA-typed patients to analyze their microbiota compositions via 16S RNA gene sequencing. Results Of the 964 patients, the male:female ratio was 114:850, and 342 of these patients (35.5%) had already developed liver cirrhosis (LC) before enrollment. Patients with PBC showed a significantly higher frequency of HLA DRB1*08:03 than did the controls (21.2% vs. 9.0%, P=0.0001). HLA-DRB1*03:01, DRB1*07:01, DRB1*14:05, and DRB1*14:54 frequencies were also increased but did not reach significance after Bonferroni’s correction. Conversely, the DQB1*03:01 frequency was significantly lower in patients with PBC than in the controls (24.5% vs. 39.2%, P=0.0010). The patients’ gut microbiota were analyzed from four perspectives. The microbial community abundances were significantly lower in FHRAC-positive patients (patients with a combination of five HLA DRB1 high-risk alleles) than in FHRAC-negative patients (P<0.05). Of the top 10 microbial genera, Lachnospiraceae_incertae_sedis was higher in the FHRAC-positive patients than in the FHRAC-negative patients (P<0.05). linear discriminant analysis (LDA) effect-size (LEfSe) analysis showed different microbes at different levels in the FHRAC-negative patients but not in the FHRAC-positive patients. DQB1*03:01-positive patients contained mostly Lactobacillaceae at the family level. A comparison of the FHRAC-positive patients with and without liver cirrhosis showed that the abundances of Veillonella were significantly higher in patients with cirrhosis and FHRAC than in those without cirrhosis and are FHRAC-negative. Conclusion The HLA class II genes may influence the gut microbiota compositions in patients with PBC. Differential gut microbiota were expressed at different taxonomic levels. Some bacterial abundances may be increased in FHRAC-positive patients with PBC and cirrhosis.